Impact of Poor Internet Connectivity on Electronic Library Services and the Development of Offline-Accessible Digital Library Software - Onyebuchi Lynda Emmachika; Agatha Ujunwa Nnatu; Ngozi Njideka Okechukwu (PT. Altaf Publishing Corp, 2026)
Inadequate internet connectivity has become a major barrier to the effective use of electronic library services in tertiary institutions, restricting access for students, lecturers, researchers, and librarians. This study employed a quantitative descriptive survey design to examine the impact of poor internet connectivity on electronic library services and its implications for the development of offline-accessible digital library software. The study was conducted in selected tertiary institutions, with a purposive sample of 76 respondents comprising students, lecturers, researchers, and librarians. Data were collected using a structured questionnaire validated by experts, yielding a Cronbach’s Alpha reliability coefficient of 0.87. Responses were gathered online via Google Forms and analyzed using SPSS through descriptive statistics and inferential analyses, including correlation, regression, and ANOVA at a 0.05 significance level. Findings revealed that poor internet connectivity significantly limits access to electronic library resources due to frequent network interruptions, inadequate internet speed, and disruptions to research activities. Connectivity challenges also affect the reliability and stability of electronic library services. In addition, limited internet access influences the effectiveness and quality of offline-accessible digital library software. Correlation and regression analyses indicated significant positive relationships between poor internet connectivity and both electronic library service performance and offline digital library software development, with no evidence of multicollinearity. The study concludes that improving internet infrastructure alongside integrating offline-accessible digital library solutions is crucial for enhancing access, service quality, and user satisfaction in tertiary institutions.